Developmental Modes and Developmental Mechanisms can Channel Brain Evolution - Charvet, Christine J.; Striedter, Georg F. (Frontiers in Neuroanatomy, 2011)
Anseriform birds (ducks and geese) as well as parrots and songbirds have evolved a disproportionately enlarged telencephalon compared with many other birds. However, parrots and songbirds differ from anseriform birds in their mode of development. Whereas ducks and geese are precocial (e.g., hatchlings feed on their own), parrots and songbirds are altricial (e.g., hatchlings are fed by their parents). We here consider how developmental modes may limit and facilitate specific changes in the mechanisms of brain development. We suggest that altriciality facilitates the evolution of telencephalic expansion by delaying telencephalic neurogenesis. We further hypothesize that delays in telencephalic neurogenesis generate delays in telencephalic maturation, which in turn foster neural adaptations that facilitate learning. Specifically, we propose that delaying telencephalic neurogenesis was a prerequisite for the evolution of neural circuits that allow parrots and songbirds to produce learned vocalizations. Overall, we argue that developmental modes have influenced how some lineages of birds increased the size of their telencephalon and that this, in turn, has influenced subsequent changes in brain circuits and behavior.